Effect of Sport Intervention on Positive and Negative Symptoms in Schizophrenic Patient at AL-Rashad Mental hospital - Ghada Adeab; Dhelal Ahmed; naama hamady; Rathwan Altuhafy (مجلة الرافدين للعلوم الرياضية, 2021)
Schizophrenia , is a chronic mental disorder. The treatment strategies  include medication and many types of psychotherapy, but  these can have limited effects in the most affected patients. Sport therapy may provide a mean of improving mental health among people with schizophrenia.  The aim of this study is to examine the effect  of sport intervention  on the Positive and Negative Symptom Scale (PANSS) of the inpatients diagnosed with schizophrenia. Subjects and methods of study was conducted at AL Rashad Hospital in the city of Baghdad  for  6   months. It is a single blind randomized controlled trial. 100 male patients between the age of 18-59 years with a diagnosis of schizophrenia according to DSM-5 criteria for at  least 2 years duration prior to the beginning  of the study were randomly included. The study group underwent training sessions followed by competitions in games need interaction . Results show that  total  PANSS scores for the study group were significantly lower than those for the controls group, comparisons also showed that sport  intervention  affords significant advantages on general psychosocial functioning .Conclusions participation in sport may reduce the psychiatric symptoms in patients with chronic schizophrenia, less relapse and less consuming of different antipsychotic medications.